2011
DOI: 10.1007/s00586-011-1794-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of MRI-defined spinal pathoanatomies and their association with Modic changes in individuals seeking care for low back pain

Abstract: Modic changes are of increasing interest, however their age and gender prevalence are not well described. To date, the associations between Modic changes and other common vertebral pathologies have only been described in small samples (n \ 100). Our aim was, in a large dataset of people with low back pain, to (1) describe the prevalence of a range of spinal pathoanatomies, and (2) examine the association between Modic changes and stages of intervertebral disc (IVD) pathology. Common pathologies were coded from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 35 publications
4
64
1
Order By: Relevance
“…Although diagnostic codes were not available in the data from either setting, SBT was originally validated in people diagnosed by GPs as having non-specific LBP. In our secondary care setting, approximately 45 % have MRI evidence of central stenosis or nerve root compromise [16] and this may have affected their recovery trajectories and, thereby, the predictive ability of the SBT. Another potential factor affecting the predictive ability could be a social class bias that we believe results in an over-representation of lower sociodemographics in the secondary care cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although diagnostic codes were not available in the data from either setting, SBT was originally validated in people diagnosed by GPs as having non-specific LBP. In our secondary care setting, approximately 45 % have MRI evidence of central stenosis or nerve root compromise [16] and this may have affected their recovery trajectories and, thereby, the predictive ability of the SBT. Another potential factor affecting the predictive ability could be a social class bias that we believe results in an over-representation of lower sociodemographics in the secondary care cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This inclusion criteria resulted in 20.8 % (250 patients) otherwise eligible patients being excluded. No diagnostic data were available in the database but using magnetic resonance imaging to document the presence of lumbar patho-anatomic findings, previous descriptive research on this clinical population showed that approximately 0.5 % or less have serious pathology (tumour, fracture, tuberculosis), 15 % have central stenosis, 29 % have nerve root compromise and the remainder have nonspecific LBP [16].…”
Section: Methodsmentioning
confidence: 99%
“…Lumbar disc degeneration and herniation is regarded as a risk factor for developing MC, especially MC I [7][8][9]. Patients with lumbar disc herniation often have a combination of low back pain and radicular pain.…”
Section: Introductionmentioning
confidence: 99%
“…A further systematic review in the same year from Shanghai [7] identified two possible pathophysiological mechanisms for Modic changes-one biomechanical and one biochemical. A biomechanical pathway for development of Modic changes was supported by a large population MRI scan study in 2011 [8].…”
Section: The Factsmentioning
confidence: 95%
“…A further systematic review in the same year from Shanghai [7] identified two possible pathophysiological mechanisms for Modic changes-one biomechanical and one biochemical. A biomechanical pathway for development of Modic changes was supported by a large population MRI scan study in 2011 [8].Against this background two key papers were then published in this journal in 2013. In one study [2] Albert and colleagues established a strong relationship between…”
mentioning
confidence: 95%